The new V-Model of 2206 and its validation - Gräßler, Iris; Hentze, Julian (at-Automatisierungstechnik 68(5))

Review Hagengruber Le Ru Émilie Du Châtelet Philosophe - Hagengruber, Ruth (H-France Net)

Informationskompetenz durch E-Learning? Durch Lernvideos nach Literatur suchen - Hahn, Charlotte Anna (die hochschullehre)
The aim of this study was to find out whether teaching how to search for literature would be more beneficial to students and teachers if done online through short videos rather than in person during course time. To find out whether online videos are more beneficial, two courses were asked to fill in questionnaires, one at the beginning and one at the end of the semester. One of the courses received the input online via videos and were given an exercise to put the newly learned skills to use, the other course served as a control group and learned how to search for literature during the course. The results show that while the difference between the two groups is not significant, the videos can still be regarded as being more beneficial than teaching the necessary skills during course time.
Keywords: E-Learning; information competence; literature; library; research

Rezension zu: Bernardo Bátiz-Lazo: Cash and Dash. How ATMs and Computers Changed Banking - Schmitt, Martin (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Keywords: Wirtschaftsgeschichte; Bankengeschichte; Geldautomat; ATM; Geschichte; Technikgeschichte

Dietary sugars and cardiometabolic risk factors: a network meta-analysis on isocaloric substitution interventions - Schwingshackl, Lukas; Neuenschwander, Manuela; Hoffmann, Georg; Buyken, Anette; Schlesinger, Sabrina (The American Journal of Clinical Nutrition)
ABSTRACT Background There is controversy on the relevance of dietary sugar intake for cardiometabolic health. Objective The aim of this network meta-analysis (NMA) was to assess how isocaloric substitutions of dietary sugar with other carbohydrates affect cardiometabolic risk factors, comparing different intervention studies. Methods We included randomized controlled trials (RCTs) investigating the isocaloric effect of substituting dietary sugars (fructose, glucose, sucrose) with other sugars or starch on cardiometabolic risk markers, including LDL cholesterol, triacylglycerol (TG), fasting glucose (FG), glycated hemoglobin (HbA1c), insulin resistance (HOMA-IR), uric acid, C-reactive protein (CRP), alanine transaminase (ALT), aspartate transaminase (AST), and liver fat content. To identify the most beneficial intervention for each outcome, random-effects NMA was conducted by calculating pooled mean differences (MDs) with 95% CIs, and by ranking the surface under the cumulative ranking curves (SUCRAs). The certainty of evidence was evaluated using the Confidence In Network Meta-Analysis tool. Results Thirty-eight RCTs, including 1383 participants, were identified. A reduction in LDL-cholesterol concentrations was shown for the exchange of sucrose with starch (MD: −0.23 mmol/L; 95% CI: −0.38, −0.07 mmol/L) or fructose with starch (MD: −0.22 mmol/L; 95% CI: −0.39, −0.05 mmol/L; SUCRAstarch: 98%). FG concentrations were also lower for the exchange of sucrose with starch (MD: −0.14 mmol/L; 95% CI: −0.29, 0.01 mmol/L; SUCRAstarch: 91%). Replacing fructose with an equivalent energy amount of glucose reduced HOMA-IR (MD: −0.36; 95% CI: −0.71, −0.02; SUCRAglucose: 74%) and uric acid (MD: −23.77 µmol/L; 95% CI: −44.21, −3.32 µmol/L; SUCRAglucose: 93%). The certainty of evidence was rated very low to moderate. No significant effects were observed for TG, HbA1c, CRP, ALT, and AST. Conclusions Our findings indicate that substitution of sucrose and fructose with starch yielded lower LDL cholesterol. Insulin resistance and uric acid concentrations were beneficially affected by replacement of fructose with glucose. Our findings are limited by the very low to moderate certainty of evidence. This review was registered at www.crd.york.ac.uk/prospero as CRD42018080297.

Narratives of Vicarious Experience in Oral History Interviews with Craft Artists - Mildorf, Jarmila (Journal of Pragmatics)

Relation of dietary glycemic index, glycemic load, added sugar intake, or fiber intake to the development of body composition between ages 2 and 7 y - Buyken, Anette; Cheng, Guo; Günther, Anke LB; Liese, Angela D; Remer, Thomas; Karaolis-Danckert, Nadina (The American Journal of Clinical Nutrition)

Effects of breastfeeding on health outcomes in childhood: beyond dose-response relations - Buyken, Anette; Karaolis-Danckert, Nadina; Günther, Anke; Kersting, Mathilde (The American Journal of Clinical Nutrition)

Zwischen Wissenschaft und Lebenswelt. Entwicklung, Stand und Zukunftsperspektiven haushaltsbezogener Bildung. - Schlegel-Matthies, Kirsten

Dietary micronutrient intake during pregnancy is a function of carbohydrate quality - Goletzke, Janina; Buyken, Anette; Louie, Jimmy CY; Moses, Robert G; Brand-Miller, Jennie C (The American Journal of Clinical Nutrition)

WHO guidelines for a healthy diet and mortality from cardiovascular disease in European and American elderly: the CHANCES project - Jankovic, Nicole; Geelen, Anouk; Streppel, Martinette T; de Groot, Lisette CPGM; Kiefte-de Jong, Jessica C; Orfanos, Philippos; Bamia, Christina; Trichopoulou, Antonia; Boffetta, Paolo; Bobak, Martin; Pikhart, Hynek; Kee, Frank; et al. (The American Journal of Clinical Nutrition)

Association between carbohydrate quality and inflammatory markers: systematic review of observational and interventional studies - Buyken, Anette; Goletzke, Janina; Joslowski, Gesa; Felbick, Anna; Cheng, Guo; Herder, Christian; Brand-Miller, Jennie C (The American Journal of Clinical Nutrition)

The link between dietary glycemic index and nutrient adequacy - Louie, Jimmy Chun Yu; Buyken, Anette; Brand-Miller, Jennie C; Flood, Victoria M (The American Journal of Clinical Nutrition)

Consumption of polyunsaturated fatty acids, fish, and nuts and risk of inflammatory disease mortality - Gopinath, Bamini; Buyken, Anette; Flood, Victoria M; Empson, Marianne; Rochtchina, Elena; Mitchell, Paul (The American Journal of Clinical Nutrition)

Como podemos definir vigilância? - Fuchs, Christian (MATRIZes)

Relation of isoflavones and fiber intake in childhood to the timing of puberty - Cheng, Guo; Remer, Thomas; Prinz-Langenohl, Reinhild; Blaszkewicz, Meinolf; Degen, Gisela H; Buyken, Anette (The American Journal of Clinical Nutrition)

Carbohydrate nutrition and inflammatory disease mortality in older adults - Buyken, Anette; Flood, Victoria; Empson, Marianne; Rochtchina, Elena; Barclay, Alan W; Brand-Miller, Jennie; Mitchell, Paul (The American Journal of Clinical Nutrition)

Body fat and animal protein intakes are associated with adrenal androgen secretion in children - Shi, Lijie; Wudy, Stefan A; Buyken, Anette; Hartmann, Michaela F; Remer, Thomas (The American Journal of Clinical Nutrition)

Birth and early life influences on the timing of puberty onset: results from the DONALD (DOrtmund Nutritional and Anthropometric Longitudinally Designed) Study - Karaolis-Danckert, Nadina; Buyken, Anette; Sonntag, Antje; Kroke, Anja (The American Journal of Clinical Nutrition)

Glycemic index in overweight development: distinguishing limited evidence from limits in evidence - Buyken, Anette; Günther, Anke LB; Barclay, Alan; Brand-Miller, Jennie; Schulze, Matthias B (The American Journal of Clinical Nutrition)